Parenting Education sebagai Upaya Meningkatkan Kualitas Pengasuhan bagi Ibu Anak Berkebutuhan Khusus di Rumah Latih Dinas Sosial Kabupaten Trenggalek - Ni’mah, Putri Khoirun; Nugroho, Rivo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
The awareness of mothers to provide the best care for children with special needs is still lacking. The purpose of this study was to describe and analyze the implementation, supporting factors, and inhibiting factors of the parenting education program as an effort to improve parenting for mothers of children with special needs at Rumah Latih. This research uses a descriptive qualitative approach. Data collection techniques in this study used in-depth interview methods, participatory observation, and documentation. Informants in this study were program managers, facilitators, and mothers of children with special needs. Data analysis used data reduction, data presentation, and conclusion drawing. The data validity tests used were source triangulation and member check, transferability, dependability, and confirmability. The results showed that the implementation of the parenting education program at the training house can improve the quality of parenting for mothers of children with special needs, indicated by using the stages of planning, implementation, and evaluation. The implementation is supported by several factors including parents, family, community, government, facilities and infrastructure, facilitators, program managers, and budget. There are also inhibiting factors, namely parents who are less cooperative, the topography of the area, and the community's ability to reach facilities.